2021
DOI: 10.3390/nu13103585
|View full text |Cite
|
Sign up to set email alerts
|

FTO and PLAG1 Genes Expression and FTO Methylation Predict Changes in Circulating Levels of Adipokines and Gastrointestinal Peptides in Children

Abstract: Adipokines and gastrointestinal tract hormones are important metabolic parameters, and both epigenetic factors and differential gene expression patterns may be associated with the alterations in their concentrations in children. The function of the FTO gene (FTO alpha-ketoglutarate dependent dioxygenase) in the regulation of the global metabolic rate is well described, whereas the influence of protooncogene PLAG1 (PLAG1 zinc finger) is still not fully understood. A cross-sectional study on a group of 26 childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 83 publications
0
5
0
Order By: Relevance
“…Detection of MRD during remission induction and consolidation therapy is the most sensitive method to evaluate treatment response and one of the strongest predictors of outcome in childhood acute lymphoblastic leukemia. Several studies have demonstrated the prognostic significance of measuring MRD in childhood ALL, suggesting that MRD positivity at serial time points during the treatment is highly predictive of relapse, and associated with poor treatment outcome ( 29 , 30 ). A recent study suggested that MRD levels at the end of remission induction therapy measured using multiparameter flow cytometry have clinical significance in childhood ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Detection of MRD during remission induction and consolidation therapy is the most sensitive method to evaluate treatment response and one of the strongest predictors of outcome in childhood acute lymphoblastic leukemia. Several studies have demonstrated the prognostic significance of measuring MRD in childhood ALL, suggesting that MRD positivity at serial time points during the treatment is highly predictive of relapse, and associated with poor treatment outcome ( 29 , 30 ). A recent study suggested that MRD levels at the end of remission induction therapy measured using multiparameter flow cytometry have clinical significance in childhood ALL.…”
Section: Discussionmentioning
confidence: 99%
“…The path association may be related to genetic and epigenetic factors. Studies reported that the expression level of fat mass and obesity associated gene (FTO) and pleomorphic adenoma gene 1 (PLAG1) genes associated with obesity was significantly related to the concentration of leptin (55,56).…”
Section: Discussionmentioning
confidence: 99%
“…Another additional explanation for our results may be related to the fact that epigenetic factors and differential gene expression patterns are associated with variations in the concentrations of leptin ( 17 ). In fact, in a recent publication, a different expression level of the FTO gene, extensively described as linked to obesity, has been related to the concentration of hormones produced by the adipose tissue, being positively correlated with leptin ( 18 ). Moreover, higher FTO expression has been associated with an increase of the concentration of FFA, suggesting that the FTO gene may play a role in the development of the impairment of glucose-lipid metabolism related to obesity in children ( 19 ).…”
Section: Discussionmentioning
confidence: 99%